2010
DOI: 10.1016/j.nima.2010.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the LIGO gravitational wave detectors in the fifth science run

Abstract: a b s t r a c tThe Laser Interferometer Gravitational Wave Observatory (LIGO) is a network of three detectors built to detect local perturbations in the space-time metric from astrophysical sources. These detectors, two in Hanford, WA and one in Livingston, LA, are power-recycled Fabry-Perot Michelson interferometers. In their fifth science run (S5), between November 2005 and October 2007, these detectors accumulated one year of triple coincident data while operating at their designed sensitivity. In this pape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 27 publications
0
115
0
Order By: Relevance
“…Calibration errors, which can influence the reconstructed amplitude, phase, and timing of the data [31], have the potential to affect parameter-estimation results. An analysis of the effect of calibration errors, which considered mock errors similar to those expected during the S6 and VSR2/3 runs, concluded that such errors are unlikely to cause a significant deterioration in parameter-estimation accuracy [33] at the moderate SNRs considered in this paper.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibration errors, which can influence the reconstructed amplitude, phase, and timing of the data [31], have the potential to affect parameter-estimation results. An analysis of the effect of calibration errors, which considered mock errors similar to those expected during the S6 and VSR2/3 runs, concluded that such errors are unlikely to cause a significant deterioration in parameter-estimation accuracy [33] at the moderate SNRs considered in this paper.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The fact that gravitational waveforms used in the analysis are an approximation to the actual radiation produced by astrophysical sources and that the measured strain is affected by the uncertainties in the instrument calibration [31][32][33] represent additional challenges for making robust inferences on the underlying physics. To study parameter estimation in this regime, we have analyzed several artificial compact binary coalescence (CBC) signals added to real detector data, including the ''blind'' injection described above, added both in hardware and software to the data collected by the two LIGO instruments (Hanford and Livingston) and the Virgo detector during the most recent joint science run, S6/VSR2-3.…”
Section: Introductionmentioning
confidence: 99%
“…Black hole (BH)-neutron star (NS) binary coalescences are among the prime sources of gravitational waves (GWs) for ground-based detectors, such as Advanced LIGO, Advanced Virgo, and KAGRA [1][2][3]. Gravitaional waves from BH-NS binaries will enable us to probe the supranuclear-density matter [4,5] and cosmological expansion [6] via the NS tidal effect even without electromagnetic (EM) observation.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in the calibration of GW detectors (Abadie et al 2010a;Accadia et al 2011) may impact the ability to correctly choose the right fields to observe with EM instruments. To estimate the potential detriment to pointing, we generated a second set of simulated burst signals, with each signal including some level of miscalibration corresponding to realistic calibration errors.…”
Section: Calibration Uncertaintymentioning
confidence: 99%